2022
DOI: 10.1177/00207640221089535
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of smartphone addiction among Asian medical students: A meta-analysis of multinational observational studies

Abstract: Background: High prevalence of smartphone addiction among medical students may contribute to adverse physical and mental health outcomes. Aim: To estimate the prevalence of smartphone addiction, and explore the influencing factors and related mental health symptoms of smartphone addiction among Asian medical students. Design: Systematic review and meta-analysis. Methods: PubMed (MEDLINE), the Cochrane Central Register of Controlled Trials, and EMBASE were searched for relevant literature from the inception to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 65 publications
0
26
2
Order By: Relevance
“…It has been observed that SA has worryingly increased worldwide in recent years. Zhong et al ( 2 ) conducted a systematic review and found that the prevalence of SA among Asian medical students was 41.93%. Meng et al ( 3 ) found that the global pooled prevalence of SA was 34.5% among college and high school student populations over the last 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that SA has worryingly increased worldwide in recent years. Zhong et al ( 2 ) conducted a systematic review and found that the prevalence of SA among Asian medical students was 41.93%. Meng et al ( 3 ) found that the global pooled prevalence of SA was 34.5% among college and high school student populations over the last 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other adults, mobile phone addiction has a very high incidence among young college students [ 8 ]. The prevalence of mobile phone addiction among Asian medical students was as high as 41.93% [ 9 ]. Studies have shown that medical students mainly suffer from academic pressure because of too many courses [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medical students' sleep quality is poor due to late-night studying [11,12], a bad dormitory environment [13], excessive use of electronic devices before bedtime [14,15], and internship shifts [16]. The study showed that the prevalence of sleep disturbance among medical students is higher than that among nonmedical students and the general population [17].…”
Section: Introductionmentioning
confidence: 99%